Concept and considerations of a medical device: the active noise cancelling incubator - Jaschke, Artur C.; Bos, Arend F. (Frontiers in Pediatrics, 2023)
An increasingly 24/7 connected and urbanised world has created a silent pandemic of noise induced hearing loss. Ensuring survival to children born (extremely) preterm is crucial. The incubator is a closed medical device, modifying the internal climate, and thus providing an environment for the child, as safe, warm, and comfortable as possible.While sound outside of the incubator is managed and has decreased over the years, managing the noise inside of the incubator is still a challenge.Using Active Noise Cancelling in an incubator will eliminate unwanted sounds (i.e., from the respirator and heating) inside of the incubator, and by adding sophisticated algorithms, normal human speech, NICU music based therapeutic interventions and natural sounds will be sustained for the child in the pod. Applying different methods such as Active noise Cancelling, Motion Capture, Sonological Engineering as well as sophisticated Machine Learning algorithms, will be implemented in the development of the incubator.A Controlled and active sound environment in and around the incubator can in turn promote the well-being, neural development and speech development of the child and minimise distress caused by unwanted noises. While developing the hardware and the software pose individual challenges, it is about system design and aspects contributing to it. On the one hand it is crucial to measure the auditory range and frequencies in the incubator, as well as the predictable sounds that will have to be played back into the environment. On the other, there are many technical issues which have to be addressed when it comes to algorithms, datasets, delay, microphone technology, transducers, convergence, tracking, impulse control and noise rejection, noise mitigation stability, detection, polarity and performance.Solving a complex problem like this, however, requires a de-disciplinary approach, where each discipline will realise its own short-comings and boundaries, and in turn will allow for innovations and new avenues. Technical developments used for building the ANC-Incubator have the potential to contribute to improved care solutions for patients, both infants and adults.